A Method for User Centering Systematic Product Development Aimed at Industrial Design Students - Coelho, Denis A. (Design and Technology Education: An International Journal, 2010)
Instead of limiting the introduction and stimulus for new concept creation to lists of specifications, industrial design students seem to prefer to be encouraged by ideas in context. A new method that specifically tackles human activity to foster the creation of user centered concepts of new products was developed and is presented in this article. This approach supports to push the limits of creativity to get passed existing concepts. This article stresses important aspects of established literature about the process of developing products, highlighting how the requirements of the specification are encouraged as a first step in creating new concepts. The theory about activity, developed by Leontiev and Vygotsky, can fundamentally be used to the benefit of many examples of human activity. Systematic design procedures are also used in the method presented to evaluate and improve the initial concept drafts and guide their development.